Immiserising growth and mobility of capital with and without land in Harris-Todaro model. (1st January 2013) - Inoue, Tadashi
Under various frameworks of Harris-Todaro two sector models, the effects of the change in capital, population and land on outputs, employment of labour, employment ratio of urban sector and welfare are examined. The possibility of immiserising growth is seen to give rise with tariff ridden imports and foreign capital inflow with or without full interest payment repatriation for both sector specific capital and mobile capital irrespective of the existence of land in production function.